The Gravity Model in International Business - A bibliometric analysis: Trends, applications and future prospects - Tuñoque-Morante, Luis; Ballena-Tavara, Rodrigo; Hernandez Barrera, María Josefina; Vidal-Taboada, Silvia Lourdes; Pisfil-Benites, Nilthon (LACCEI, 2025)
In this research, a bibliometric analysis is carried out on the gravity model in international trade, covering the period from 1991 to 2024. The bibliometric mapping methodology is applied, using the Scopus database, from which 515 documents from 286 scientific journals were collected. The results show a sustained growth in scientific production since 2005, with an average of 22.63 citations per document and a participation of 1102 authors. Six relevant thematic clusters were identified that address agricultural trade, trade agreements, regional integration, non-tariff barriers and econometric methodologies such as the use of PPML. International collaboration is also highlighted, with a high participation of countries such as China, the United States, Germany and Spain, as well as prominent institutions such as the University of Novi Sad and Beijing Forestry University. The reference spectroscopy technique allowed the identification of three seminal works published in 1962, 2003 and 2020, which marked key milestones in the theoretical and methodological evolution of the model. It is concluded that the gravity model has established itself as a robust and versatile tool in the analysis of international trade, with an increasingly global, collaborative and methodologically advanced approach.